The Influence of Digital Texts on Eighth Graders' Reading Comprehension - Irwanto, Wahyu Risa Arisca; Darmawan; Wahyudin; Aminah (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aims to determine whether there is a significant influence of digital text on reading comprehension the eighth-grade students of SMP Negeri 20 Palu. This study used a quasi-experimental design, namely 32 students of class VIII A and 29 students of class VIII B, and were classified into experimental and control classes. The experimental class was taught using digital text while the control class was taught using printed text. In addition, this study was conducted through the following procedures: pre-test, treatment, and post-test. Data were collected through a reading test. There was a significant difference between students who were taught using digital text and those who were taught using printed text. This can be seen from the results of the post-test. The mean score in the experimental class is 81.77 and the mean score in the control class is 70.35. The data were analyzed using inferential statistics, including the independent sample t-test. From the results of the t-test, a significance value of 0.000 was obtained which was smaller than the standard significance value, meaning that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Finally, it can be concluded that digital text is effective for reading comprehension.